0012 Utilising health literacy in chronic disease and injury prevention. (26th April 2015) - Wyant, Brian; Smith, Andrea
Abstract : Statement of purpose: Literacy is a stronger predictor of an individual's health status than age, income, employment status, education level or racial/ethnic group. To improve health literacy and encourage patient-provider communication among cardiovascular patients aged 50 and older, Pennsylvania has partnered with the Health Care Improvement Foundation (HCIF) to provide health literacy training to providers and patient activation training to senior groups in Southeast Pennsylvania. Methods/Approach: The strategy took a multi-prong approach: Conduct health literacy trainings for providers/staff from health systems focusing on oral communication, materials development, e-health, and advocacy efforts. Train adults from senior groups as peer educators to provide patient activation in Senior Centres, ESL classes, and other community venues. Provide mini-grants to hospitals to pilot programs, modify materials, or address e-health needs as they relate to health literacy. Results: To date, the program has trained 69 peer educators, 334 adult health care consumers have received patient activation/education, 4, 750 providers have been trained in effective patient-provider communication, and 34 cardiovascular health literacy interventions have been implemented at 10 hospitals. Through collaborative efforts with the Hospital and Health System Association (HAP), HCIF expanded health literacy training statewide. HAP conducted the trainings at an additional 25 hospitals around the state that trained 1, 878 providers. Conclusions: HCIF is involved with 10 hospitals that are creatively implementing ways to improve communication with their patients. Partnership with these hospitals and with HAP will continue and expansion will occur to four community organisations that work with the Pennsylvania Immigration and Citizenship Coalition to provide patient activation to members of multilingual communities. Significance and contribution to the field: Providing health literacy education and training to health care providers and patients will improve prevention efforts for chronic disease and injury. Associated costs will be reduced as health literacy also leads to reduced readmission rates.